Knowledge and stated practice of contraception among adult married males in Bishnupur-II block, South 24 Parganas, West Bengal - Karmakar, Anil; Pal, Jayita; Ghosh, Manoj; Pramanik, Mrinal Kanti; Mahato, Bappadittya; Gayen, Ram Krishna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Contraception is pivotal in reproductive health and family planning, yet knowledge gaps persist among married males, impacting public health outcomes. This study aimed to evaluate contraceptive knowledge and practices and identify determinants among 127 married males in Bishnupur-II block, South 24 Parganas. Methods: This community-based cross-sectional study utilised simple random sampling. Data were collected via house-to-house visits using a semi-structured questionnaire and analysed with SPSS version 21.0. Results: Participants exhibited significant knowledge gaps, notably among those with lower education levels. Age, religion, education, and comfort in discussing contraception with partners emerged as associated factors. Participants comfortable discussing contraception showed higher knowledge and practice odds. Conclusions: Addressing knowledge gaps and enhancing contraceptive practices necessitate multifaceted interventions emphasising education, partner communication, counselling, and targeted initiatives. Implementation of these recommendations is expected to bolster reproductive health outcomes and community well-being.